Ethics and Religious Authority in The Age of Artificial Intelligence: a Study on The Da’wah Narratives of NU Online - Rohman al-Manduri; Dian Wulan Sari; Nadia Cahaya Amanda; Muhammad Hafizul Arifin (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
The rapid development of artificial intelligence (AI) has reshaped the dynamics of religious communication, compelling Islamic institutions to reconfigure how ethical and authoritative discourses are maintained in digital environments. This study investigates how Nahdlatul Ulama (NU) Online, the official digital platform of Indonesia’s largest Islamic organization, constructs and sustains ethical and authoritative Islamic discourse in the age of AI. Employing a qualitative approach that integrates content analysis and digital ethnography, the research examines 247 online articles, 63 video sermons, 89 social media posts, and 34 official statements published between 2022 and 2025, complemented by in-depth interviews with 12 NU Online editors, content creators, and contributing ulama. The findings reveal three interconnected strategies through which NU Online navigates AI-mediated da’wah: first, anchoring technological discourse within Islamic ethical frameworks, particularly akhlakul karimah (noble character) and wasathiyyah (moderation); second, adopting a hybrid model of authority that merges traditional scholarly legitimacy (isnad) with algorithmic optimization to enhance digital visibility; and third, addressing the tension between authenticity and accessibility through editorial control, contextual framing, and the promotion of digital literacy as a moral and religious duty. However, the study also identifies a paradox: while NU Online successfully maintains authoritative discourse within its institutional platforms, the increasing circulation of user-generated and AI-produced religious content challenges interpretive coherence and institutional control. The findings contribute to ongoing debates on religious authority, digital ethics, and the governance of AI in Islamic contexts, emphasizing that the preservation of religious authenticity in the digital age depends not on technological resistance but on critical, values-driven engagement. The study offers a novel contribution by elucidating how traditional Islamic principles of akhlaq, isnad, and wasathiyyah are recontextualized in algorithmically mediated spaces, thereby advancing the conceptual understanding of “algorithmic authority” in contemporary Islamic media.